500-Year Records Demonstrating a Sharp Increase in Intensities of Three Natural Hazards at Multiple Spatiotemporal Scales in China - Wang, Zhaohua; Yuan, Jingxiang; Peng, Yu; Wang , Chengru; Li, Guoying (The Global Environmental Engineers, 2023)
China has experienced frequent natural disasters, including droughts, floods, and heavy snowfall. This study discusses the temporal-spatial patterns in the country since 1500. The intensity of drought in Henan and Inner Mongolia was higher than that in Guizhou and Qinghai, while little difference in flood intensity was observed among these provinces. The intensity of snow disasters in Qinghai was much higher. Except for the slightly decreasing drought trend in Henan, the three natural disasters showed a significant increase over time. Drought disasters in Guizhou, Henan, and Qinghai showed few seasonal differences, whereas those in Inner Mongolia mostly occurred in winter and spring. Floods were concentrated during the summer, while snow disasters occurred mainly during winter and spring. According to the Mann–Kendall (M–K) test, the seasonal differences in disaster trends in Guizhou, Henan, and Qinghai were unclear and similar to the overall trend. However, the disaster trends in Inner Mongolia showed seasonal differences. The spatial distribution of natural disasters in Guizhou and Henan were similar, and their changing trends were extremely scattered, while in Inner Mongolia and Qinghai, they were clustered. The spatial distribution of disaster intensity had few seasonal differences and was similar to the overall distribution. However, when considering the spatial distribution of disaster trends by season, seasonal differences were evident. This study has provided an earlier signal on how to prevent and mitigate natural disasters based on 500 years' tempo-spatial pattern, and the measures on how to improve the management practices of natural hazards under climate change were also suggested.